Caste-gender intersectionalities in wheat-growing communities in Madhya Pradesh, India - Farnworth, Cathy Rozel; Bharati, Preeti; Krishna, Vijesh V.; Roeven, Lara; Badstue, Lone B. (Informa UK Limited, 2022)
This article addresses the patterns of women's engagement in wheat as decision-makers and laborers in India. Qualitative research conducted twice in one village in Madhya Pradesh explored gender norms and agency changes over time. Quantitative research was carried out in the same village and 17 additional villages. Four questions are asked: (1) Is decision-making in wheat feminized? (2) Is labor in wheat feminized? (3) In what ways do interactions between caste and gender determine and limit the spaces within which women can act? (4) In what ways are women challenging their gender and caste identities to enhance their livelihoods by influencing their roles, responsibilities, and decision-making in wheat? The findings show that only a few women consider themselves "farmers" and participate actively in discussions around wheat. Over the last decade, women of all castes have been employed as laborers in wheat, driven by aspirations to improve their lives. Women also fund the wheat system through self-help groups. However, their participation in the labor force is threatened by agricultural mechanization. A strong, positive association was observed between women's agency in crop production and their agency in household expenditures.